Bioethanol Production From Cellulose by Candida tropicalis, as An Alternative Microbial Agent to Produce Ethanol from Lignocellulosic Biomass - Hermansyah Hermansyah; Novia Novia; Maulin Wiraningsih (Program Pascasarjana Universitas Sriwijaya, 2016)
Abstract: Candida tropicalis isolated from Tuak is a potentially useful microorganism for the ethanol production from lignocellulosic biomass and it can be alterbative agent replacing Saccharomyces cerevisae for fermentation process. Although C.tropicalis could not convert all carbohydrates content of lignocellulosic into bioethanol, however it is able to grow on medium in the presence of either xylose or arabinose as carbon source. Our result showed that fermentation of 10 % (w/v) cellulosic as sole carbon source produced 2.88% (v/v) ethanol by C.tropicalis. This ethanol production was lower than usage of 10% (w/v) dextrose as sole carbon source medium which producing 5.51% (v/v) ethanol. Based upon our expreiment indicated that C.tropicalis is able to conduct two main process in converting of cellulosic material- to ethanol which is hydrolysis the degradation of cellulose into glucose, and fermentation the process the conversion glucose into bioethanol.Keywords : Candida tropicalis, bioethanol, fermentation, cellulosic Abstrak (Indonesian): Candida tropicalis yang diisiolasi dari Tuak adalah agen yang berpotensi dalam produksi etanol dari biomasa lignoselulosa dan dapat dijadikan agen alternatif menggantikan Saccharomyces cerevisiae pada proses fernentasi. Walaupun C.tropicalis tidak dapat mengkonversi semua kandungan karbohidrat lignoselulosamenjadi etanol, akan tetapi C.tropicalis mampu tumbuh pada media dengan xilosa atau arabinosa sebagaisumber karbon. Hasil kami menunjukkan bahwa dengan mengguankan C.tropicalis fermentasi 10% (w/v) selulosa sebagai satu-satunya sumber karbon menghasilkan 2,88% (v/v) etanol, Produksi etanol ini lebih rendah jika menggunakan 10% (w/v) dekstrosa sebagai satu satunya sumber karbon yang menghasilkan 5,51% (v/v) etanol. Berdasarkan percobaan menunjukkan bahwa C.tropicalis mampu melakukan dua proses utama dalam mengkonversi material selulosa menjadi etanol yaitu hidrolisis degradasi selulosa menjadi glukosa, dan fermentasi proses konversi glukosa menjadi bioetanol.Kata Kunci: Candida tropicalis, bioetanol, fermentasi, celulosik